The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1101/499574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Girls’ attentive traits associate with cerebellar to dorsal attention and default mode network connectivity

Abstract: Attention traits are a cornerstone to the healthy development of children's performance in the classroom, their interactions with peers, and in predicting future success and problems. The cerebellum is increasingly appreciated as a region involved in complex cognition and behavior, and moreover makes important connections to key brain networks known to support attention: the dorsal attention and default mode networks (DAN; DMN). The cerebellum has also been implicated in childhood disorders affecting attention… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 102 publications
(114 reference statements)
2
0
0
Order By: Relevance
“…The usefulness of GSR in resting-state fMRI analysis is highly debated. 48 54,56,113 Similar to others, 80 we found similar general group difference maps of ACC FC with and without GSR; however, the differences without GSR analysis, did not pass the threshold of p < 0.05. Other studies have also reported that GSR increases the likelihood of identifying significant group differences, especially where regions are negatively associated.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The usefulness of GSR in resting-state fMRI analysis is highly debated. 48 54,56,113 Similar to others, 80 we found similar general group difference maps of ACC FC with and without GSR; however, the differences without GSR analysis, did not pass the threshold of p < 0.05. Other studies have also reported that GSR increases the likelihood of identifying significant group differences, especially where regions are negatively associated.…”
Section: Discussionsupporting
confidence: 89%
“…[77][78][79] We found evidence of increased negative perigenual ACC FC with the cerebellum in children with PTH (compared to controls). As increased ventral ACC FC to the cerebellum has previously been associated with attention problems, 80 the increased pACC-cerebellum FC seen in our study could suggest dysregulated attentional modulation of pain.…”
Section: Discussionsupporting
confidence: 72%